Effect of Intrinsic Motivation on Affective Responses during and after Exercise: Latent Curve Model Analysis. Issue 3 (December 2014) - Shin, Myoungjin; Kim, Inwoo; Kwon, Sungho
Understanding the relationship between affect and exercise is helpful in predicting human behavior with respect to exercise participation. The goals of the present study were to investigate individual differences in affective response during and after exercise and to identify the role of intrinsic motivation in affective changes. 30 active male college students ( M age = 21.4yr.) who regularly participated in sports activities volunteered to answer a questionnaire measuring intrinsic motivation toward running activities and performed a 20-min. straight running protocol at heavy intensity (about 70% of VO2 max). Participants' affective responses were measured every 5 min. from the beginning of the run to 10 min. after completing the run. Latent curve model analysis indicated that individuals experienced different changes in affective state during exercise, moderated by intrinsic motivation. Higher intrinsic motivation was associated with more positive affect during exercise. There were no significant individual differences in the positive tendency of the participants' affective responses after exercise over time. Intrinsic motivation seems to facilitate positive feelings during exercise and encourages participation in exercise.